Rare Co-occurrence of Ocular Myasthenia Gravis and Thyroid-Associated Orbitopathy (Ophthalmopathy) in an Individual With Hypothyroidism - An, Ran; Li, Yan; Yang, Baiyuan; Wang, Hui; Xu, Yanming (Frontiers in Endocrinology, 2019)
Ocular myasthenia gravis (Ocular MG, OMG) shares many clinical features with thyroid-associated orbitopathy or thyroid-associated ophthalmopathy (TAO). In the rare instance of their coexistence, clinicians may fail to diagnose ocular MG when TAO is also present. Here we report the case of a man presenting with TAO and ocular MG whose "hyperthyroidism" -- most likely the hashitoxicosis variant of Hashimoto's thyroiditis -- rapidly transformed to hypothyroidism after radioactive iodine therapy. This is reminiscent of a previous case of a patient with MG in whom disease onset coincided with methimazole-induced transformation from hyper- to hypothyroidism. It is possible that the same transformation from "hyper-" to hypothyroidism in our patient, which occurred after radioactive iodine therapy and was accompanied by hypothyroidism-associated orbitopathy (ophthalmopathy), may have induced the development of myasthenia gravis,The hypothyroidism may have been caused by the radioactive iodine therapy and/or it may simply reflect the natural course of the hashitoxicosis variant of Hashimoto's thyroiditis. The co-occurrence of hypothyroidism, hypothyroidism-associated orbitopathy (ophthalmopathy) and ocular MG has never been reported. Our case highlights the need for clinicians to focus on symptoms overlapping between hyperthyroidism and the hashitoxicosis variant of Hashimoto's thyroiditis, and to diffentiate carefully between them, especially when deciding on radioactive iodine therapy. In addition, our case highlights that the possible co-occurrence of TAO should be considered if a patient with thyroid disease presents with both ptosis and eye movement dysfunction, and only the ptosis dramatically resolves after treatment with pyridostigmine bromide.